Productivity growth in decline despite increasing workforce qualifications - Karl Brenke (DIW Weekly Report, 2019)
After developing at an increasingly slower pace over the decades, labor productivity in Germany has recently stagnated. This is in contrast to the development of the workforce's qualifications, which have been growing steadily due to rapid academicization. These phenomena can be found in other developed countries and are often attributed to sectoral change. Indeed, the shift of economic activity towards services has hampered productivity growth since the turn of the millennium, but not to a large extent. Picking up on a debate in the USA, this report looks at bureaucratization trends. For example, an analysis of German data from the European Labour Force Survey shows that jobs vital to bureaucracies have gained in importance in Germany, one possible reason for low productivity growth. Further research is needed to determine whether this link can be empirically proven and to what extent this development has contributed to the slowdown in productivity growth.
Keywords: J24; O40; I25; 330; productivity growth; academization; bureaucratization